2021
DOI: 10.21203/rs.3.rs-154364/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perianal Disease Onset Age is Associated with Need for Abdominal Surgery in Perianal Crohn’s Disease: A Ten-year Observational Study in China

Abstract: Background and aims: The significance of different ages of perianal disease (PD) onset in patients with perianal Crohn’s disease (PCD) remains unknown. We aimed to investigate the impact of paediatric-onset PD (POP, <18 years) and adult-onset PD (AOP, ≥18 years) on the Crohn’s disease (CD) course in a Chinese cohort.Methods: The medical records of the diagnosed PCD patients from 2008 to 2018 were reviewed retrospectively. The cumulative incidence of abdominal surgery was calculated using the Kaplan-Meier, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Perianal involvement has been shown in adults, and separately in children, to be associated with increased utilization of biologics and, on the other hands, increased hospitalizations (2,18–20) while there are controversial reports on surgery (18,20). A single-center retrospective Chinese study reported higher utilization of biologics in children compared to adults, but surgery risk was lower (21). Our study demonstrated worse disease outcomes in children including higher surgery rate.…”
Section: Discussionmentioning
confidence: 50%
“…Perianal involvement has been shown in adults, and separately in children, to be associated with increased utilization of biologics and, on the other hands, increased hospitalizations (2,18–20) while there are controversial reports on surgery (18,20). A single-center retrospective Chinese study reported higher utilization of biologics in children compared to adults, but surgery risk was lower (21). Our study demonstrated worse disease outcomes in children including higher surgery rate.…”
Section: Discussionmentioning
confidence: 50%